Epigallocatechin Gallate and Isoquercetin Synergize With Remdesivir to Reduce SARS-CoV-2 Replication In Vitro - Rabezanahary, Henintsoa; Badr, Ashraf; Checkmahomed, Liva; Pageau, Kim; Desjardins, Yves; Baz, Mariana (Frontiers in Virology, 2022)
The ongoing pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) urgently needs effective antivirals. After over 2 years since the beginning of the pandemic, only a few FDA approved therapeutic options are available to treat the population. Combination therapies have become a standard for the treatment of other infectious diseases such as HIV and hepatitis C due to their improved efficacy compared to monotherapy, reduced toxicity, the ability to prevent the development of resistant viral strains and their potential to treat co-infection. The interest in identifying molecules displaying bioactivity against SARS-CoV-2 has led to extensive search for promising molecules from the natural pharmacopoeia and polyphenols have been shown to display antiviral activity against a number of viruses including SARS-CoV-2. Here we evaluated the in vitro efficacy of two polyphenols, Epigallocatechin gallate (EGCG) and Isoquercetin, in combination with Remdesivir, the first-approved drug for the treatment of severe COVID-19. We confirmed the inhibitory effects of EGCG and isoquercetin against SARS-CoV-2 and demonstrated their strong antiviral synergistic effects with Remdesivir in vitro. These combinational therapies represent an interesting avenue for the treatment of COVID-19 and grant further studies.